32.4k views
4 votes
The function below is written in vertex form or intercept form. Rewrite them in standard form and show your work.

y = (x+4)(x+3)

User RTA
by
6.3k points

2 Answers

5 votes

Answer:

y = x²+7x+12

Explanation:

Given equation is :

y = (x+4)(x+3)

We have to transform above equation into standard form.

y = ax²+bx+c is standard form of quadratic equation.

y = (x+4)(x+3)

Multiply each term of first parentheses to each term of second parentheses.

y = x(x+3)+4(x+3)

y = x(x)+x(3)+4(x)+4(3)

y = x²+3x+4x+12

add the coeficients of like terms

y = x²+7x+12 is standard form of given equation.



User B Kalra
by
6.6k points
1 vote

Answer:

The standard form as
y=x^2+7x+12

Explanation:

Given: A function which is written in vertex form or intercept form.

We have to re-write it in standard form that in terms of
y=ax^2+bx+c

Given
y = (x+4)(x+3)

Multiply each term ,


y = x(x+3)+4(x+3)


y= x^2+3x+4x+12


y=x^2+7x+12

Thus , we have obtained the standard form as
y=x^2+7x+12

User Haofly
by
5.7k points